Effects of Brief Seizures on Learning - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1990)
The effects of frequent brief seizures on learning, memory, and behavior in the young animal were studied at the Department of Neurology, Children's Hospital, Harvard Medical School, Boston, MA; and Veterans Administration Medical Center and Medical College of Georgia, Augusta, GA.